AFTER BRANDI – UMBERTO BALDINI AND THE MODERN THEORY OF CONSERVATION-RESTORATION IN ITALY - Giorgio Bonsanti (Ochrona Dziedzictwa Kulturowego, 2019)
Giorgio Bonsanti, as a contemporary witness of Umberto Baldini’s professional activities in Florence and his successor as Soprintendente of the Opificio delle Pietre Dure, gives an overview of the closely intertwined situation in theory and practice of conservation-restoration at Baldini’s time. He analyses terms and principles of Baldini’s Theory and Methodological Unity and emphasises this theory as well as the related methods of reintegration as a development of Brandi’s Theory and the methods of the Istituto Centrale per il Restauro in Rome. Furthermore, he shortly outlines actual Italian positions in theory and practice of conservation-restoration.